Analisis Deret Vokal Dan Deret Konsonan Dalam Buku "Senja Di Siliwangi" - Annisa Al Dhira Jahra; Jelwita Waruwu; Bambang Hartanto (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2023)
Vowel series and consonant series are concepts in phonology that are important in Indonesian. Vowel series and consonant series affect the structure of syllables in Indonesian. Vowel series consist of vowels that line up in two different syllables, while consonant series consist of a combination of two consonants found on different syllables, albeit side by side. Both of these concepts are important to learn in Indonesian phonology learning because they can help understand the structure of syllables and phenomena such as consonant clusters and clusters. In addition, research on vowel series and consonant series in Indonesian can help enrich knowledge about Indonesian and improve Indonesian learning in the future. However, the findings may provide a deeper understanding of the structure of syllables in Indonesian, the use of language in literary works, and its impact on artistic expression and meaning in poetry. Implications of these findings could include the development of phonological theories Indonesian, the development of better Indonesian teaching guidelines, and broader application in literature and linguistics.